(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The present paper discusses current issues related to administration and government that affect e-Governance and e-Government. It considers the strategic document addressing the modernization of the Bulgarian state administration and the improvement of the judicial system functioning, as well as the implementation of e-Government in Bulgaria – the Operational Programme “Administrative Capacity”. It is part of the National Strategic Reference Framework 2007 – 2013 and contributes to achieving the following strategic objectives: 1. Enhancing economic competitiveness in terms of high and stable economic growth; 2. Stimulation of human potential by ensuring intensive employment, higher incomes and social integration. The Operational Programme has a horizontal nature and its purpose is to improve the operation of public administration directed to implementation of effective policies and quality services to citizens and businesses and creating conditions for sustained economic growth and employment, increasing professionalism and transparency, improving the functioning of the judiciary. On this basis, the priorities of the Operational Programme for achieving the strategic goals of modern administration – quality services and e-Governance – are considered.